Studi Kasus Hambatan Dan Faktor Determinan Membaca Pemahaman (Pemahaman Bacaan) Pada Siswa Kelas VIII Di Smp Negeri 20 Kota Bengkulu Dalam Menghadapi Asesmen Kompetensi Minimum (Akm) - Nadia Tusakidah, Eka; Salamah; Putri Juni Astuti, Dina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to provide an in-depth description of the barriers to reading comprehension and the determining factors that overcome them among eighth-grade students at SMP Negeri 20 in Bengkulu City in the context of preparing for the Minimum Competency Assessment (AKM) in literacy. This is a qualitative study using an intrinsic case study design. Research subjects were selected using purposive sampling, consisting of four eighth-grade students with the lowest literacy scores based on an internal AKM simulation, as well as one Indonesian language teacher. Data collection techniques included passive participant observation, structured in-depth interviews, and documentation in the form of portfolios of students’ AKM test responses. Data analysis was conducted using the interactive model by Miles, Huberman, and Saldaña, which includes data condensation, data presentation, and drawing conclusions. Data validity was tested through triangulation of techniques and sources. The research results revealed three main barriers faced by students: (1) difficulties interpreting complex syntax in the lengthy AKM stimulus texts, (2) limited proficiency in academic English, and (3) low metacognitive ability in integrating independent comprehension. The determining factors underlying these barriers include internal factors (low self-efficacy and intrinsic motivation to read) as well as external factors (a lack of exposure to multi-subject texts in the school environment and minimal family-based literacy support).